Corticospinal Modulations during Bimanual Movement with Different Relative Phases - Nomura, Yoshifumi; Jono, Yasutomo; Tani, Keisuke; Chujo, Yuta; Hiraoka, Koichi (Frontiers in Human Neuroscience, 2016)
The purpose of this study was to investigate corticospinal modulation of bimanual movement with different relative phases (RPs). The participants rhythmically abducted and adducted the right index finger (unimanual movement) or both index fingers (bimanual movement) with a cyclic duration of 1 s. The RP of bimanual movement, defined as the time difference between one hand movement and the other hand movement, was 0°, 90°, or 180°. Motor evoked potentials in the right flexor dorsal interosseous muscle elicited by transcranial magnetic stimulation were obtained during unimanual or bimanual movement. Corticospinal excitability in the first dorsal interosseous muscle during bimanual movement with 90° RP was higher than that during unimanual movement or bimanual movement with 0° or 180° RP. The correlation between muscle activity level and corticospinal excitability during bimanual movement with 90° RP was smaller than that during unimanual movement or bimanual movement with 0° or 180° RP. The higher corticospinal excitability during bimanual movement with 90° RP may be caused by the greater effort expended to execute a difficult task, the involvement of interhemispheric interaction, a motor binding process, or task acquisition. The lower dependency of corticospinal excitability on the muscle activity level during bimanual movement with 90° RP may reflect the minor corticospinal contribution to bimanual movement with an RP that is not in the attractor state.